Vitrocerâmicas condutoras de íon lítio com estrutura do tipo Nasicon baseadas no sistema Li1+X CrX (GeY Ti1-Y)2-X (PO4)3 - Nuernberg, Rafael Bianchini (2018)
The primary goal of this work is to develop a new NASICON-structured glass-ceramic with high Li-ion conductivity. Therefore, this work introduces a new series of NASICON-type compositions based on the Li1+xCrx(GeyTi1-y)2-x(PO4)3 system. At first, a specific glass-ceramic composition of this system was synthesized by the melt-quenching method, followed by crystallization. The crystallization behavior of the precursor glass was examined by differential scanning calorimetry and infrared spectroscopy. The results indicate that the precursor glass presents homogeneous nucleation, has considerable glass stability and crystallizes a NASICON-like phase, which allows solid electrolytes to be obtained by the glass-ceramic route. As a second step, we examine the effect of substituting Ti by Cr and Ge on the glass stability of the precursor glasses, on the structural parameters of NASICON-like phase and on the electrical properties of the glassceramics. Hence, a set of sixteen compositions of this system was synthesized. The results indicate that the glass stability increases when Ti is replaced by Ge and Cr. After crystallization, all the glass-ceramics present NASICON-like phase, and their lattice parameters decrease with Ge and increase with Cr content, making it possible to adjust the unit cell volume of the structure. Furthermore, the ionic conductivity and activation energy for lithium conduction in the glassceramics are notably dependent on the unit cell volume of the NASICON-type structure, achieving total ionic conductivities of up to 3x10-4 Ω−1cm−1. Finally, the electrochemical stability window of the NASICON-structured glass-ceramics of highest ionic conductivity is investigated. Cyclic voltammetry measurements were followed by in situ electrochemical impedance spectroscopy, enabling the effect of oxidation and reduction reactions on the electrical properties of the investigated glass-ceramics to be determined. X-ray photoelectron spectroscopy, in turn, was applied to determine which chemical species undergo reduction/oxidation. Our findings reveal that the electrochemical stability of this material is limited by the reduction of Ti+4 cations at low potentials and by the oxidation of O-2 anions at high potentials. A similar behavior at high potentials was also encountered for other well-known Li-ion conducting NASICON-like phosphate suggesting that the electrochemical behavior in oxidative potentials could be generalized for NASICON-structured phosphates.